Protection of Victims of Crimes in Romania: Compliance with the Legal Provisions of the European Union - Elisabeta Slabu (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2021)
Criminality is a violation of the individual rights of victims and victims of crime should be recognized and treated with respect, care and professionalism, without being discriminated against. Victims of crimes should be protected against secondary and repeated victimization, intimidation and revenge, receive adequate support in order to facilitate their recovery and have adequate access to justice. Child victims must be supported taking into account their ability to form their own opinions. States should ensure that victims with disabilities have the opportunity to enjoy their rights in full measure, as well as with other citizens, including by facilitating access to the premises where criminal proceedings take place and access to information. The Romanian state ensures, at legislative level, specialized services to victims of crime, taking into account the legal provisions adopted at the European Union level, the national legislation being convergent with the European one, but also presenting specific particularities.